ENTREPRENEURSHIP ECONOMIC SAFETY AND DEVELOPMENT OF SECURITY SERVICES - G. V. Goudkov (Модернизация, инновация, развитие)
Successful functioning of the industry that provides for safety of organizations and physical entities exercises strategic impacts on development of society and economics of any state including Russia. Economic safety of Russia is directly linked with economic and information safety of itsbusiness structures. Extension of the scope and use of services offered by experienced state and private security enterprises including licensed individuals is one of most important directions of business safety perfection. Further improvement of Russian legislation on non-governmentalsecurity structures and coordination of their activities with those of state law enforcement bodies is obligatory condition of attaining higherpublic and economic safety levels.